2012
DOI: 10.1093/occmed/kqs121
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to body fluids among health care workers in Georgia

Abstract: Data from this study can be utilized in educational programs and implementation of universal safety precautions for HCWs in Georgia to help achieve similar reductions in blood-borne infection transmission to those achieved in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
32
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 19 publications
12
32
3
5
Order By: Relevance
“…In the current study, the prevalence of HCV infection among HCWs was 4.6%, similar to the 5% HCV prevalence reported in Georgia among 1600 HCWs 12 and higher than those reported by similar studies conducted in developed as well as developing countries [13][14][15][16][17][18] which range from 0.6%-3%. This may reflect inadequate adherence of the current study's HCWs to infection control standards.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the current study, the prevalence of HCV infection among HCWs was 4.6%, similar to the 5% HCV prevalence reported in Georgia among 1600 HCWs 12 and higher than those reported by similar studies conducted in developed as well as developing countries [13][14][15][16][17][18] which range from 0.6%-3%. This may reflect inadequate adherence of the current study's HCWs to infection control standards.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with result from another study which reported 32% proportion of HCWs that always use gloves during medical procedures. 12 Current participants' infection control training was only reported by 12.5%, which is lower than that reported in India (36%). 25 In spite of the fact that training was not proven to be protective against occupational exposure, continuous effective training is encouraged to improve infection prevention.…”
Section: -22 Not For Citation Purposesmentioning
confidence: 74%
“…The rates of HBsAg and anti-HBc positivity in healthcare workers reported in several studies published in the last three decades [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] range from 0.1% to 8.1% and from 6.2% to 73.4%, respectively, depending on the age of the subjects investigated, the spread of HBV infection in their country of origin and on the prevention strategies used by the healthcare workers (Table 1). Of 5813 healthcare workers tested in Italy in 1985, 21.5% were found to be anti-HBc-positive and 1.8% HBsAg-positive [65] .…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 99%
“…Philippines 123 Case-control 8 (6.5) 81 (65.8) Aziz et al [57] NR Pakistan 250 Cross-sectional 6 (2.4) Butsashvili [58] 2006…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 99%
“…Thus, these professionals are active in financialinstitutional decisions and play their role as overseers of possible risks and of the quality of the products used, through the monitoring of the materials purchased and used in care. 12,14 To remain active, nursing needs to strengthen its professional practice based on evidence and proof, based on the fact that making a decision on whether to use a technology should involve different aspects -legal, social, ethical, political, cultural and economic. As spending in the health sector has been increasing at an overwhelming rhythm, which can affect the sustainability of health organizations and systems, the implementation of constant care assessment and monitoring strategies is fundamental.…”
Section: Discussionmentioning
confidence: 99%